Biogenic Amines and Food Safety - Martuscelli, Maria; Mastrocola, Dino (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Biogenic amines are bioactive compounds distributed in foods of all origins. Apart from their fundamental role in many bodily functions, there has recently been great interest in their toxicological potential, much research is being carried out to understand their occurrence related to both desired and undesired fermentative phenomena, chemical spoilage, low hygienic conditions, wrong handling, and criticism about technological factors of process and storage conditions. All these causes can contribute to a higher content of biogenic amines in food, particularly of those hazardous to human health. This book aims to collect scientific studies looking for new tools to limit the over-production of biogenic amines in food, search for new food sources of biogenic amines, and to spotlight the concept of safe food and bioactive amines content.